DYNAMICAL CHARACTERISTICS OF BLAST FURNACE TOP GAS RECOVERY TURBINE UNIT ROTOR (MT) - YIN JianXin; GOU YuJun; GUI YongLiang; HAN HongSheng; YANG Jie (Jixie qiangdu)
Aiming at the problems of high vibration and low efficiency of TRT rotor, the dynamic characteristics of TRT rotor are studied. The geometric modeling of the rotor is carried out by using 3D software UG, and imported into Ansys Workbench to establish a finite element analysis model; the rotor dynamic characteristics-modal, critical speed and steady-state unbalanced response are calculated and analyzed. On this basis, the finite element model is used to analyze the influence of different supporting stiffness and supporting positions on the dynamic characteristics of the rotor, and tested on the high-speed rotor test room. Research shows, the difference between calculation and test results is within 3%; the finite element analysis results can truly reflect the dynamic characteristics of the rotor. Both support stiffness and support position have a significant impact on the first and second order critical speed of the rotor. In the unbalance response, the most sensitive position of the first order is the second stage blade position, and second order is the position of the head（coupling）. A reference for the calculation and analysis of the dynamic characteristics of other rotors of the same type is provided.